Curriculum Development for Improving Mineral Exploration-Related Master Programs towards Innovation, Entrepreneurship and Social Responsibility - Sibila Borojević Šoštarić; Gabriela Paszkowska; Nils Jansson; Luis Lopes; Alberto Sanchez Miravalles; Ana Maričić; Ferenc Mádai (Materials Proceedings, 2023)
Nordic and West Balkan countries are major investment regions in Europe for greenfield and brownfield mineral exploration; however, the availability of qualified technical, scientific and managerial personnel involved in the whole mineral cycle is limited, especially in West Balkan countries. The partners of the TIMREX EIT RawMaterials-labeled MSc program have developed a joint curriculum focused on innovative raw materials prospecting and exploration methods, with strong innovation and entrepreneurial components. The program incorporates new exploration techniques and methodologies, portable and more highly sensitive equipment, robotized exploration equipment and the processing and interpreting of large, multidimensional datasets. The TIMREX curriculum was built around the ideal mineral exploration program, as suggested by raw materials stakeholders and orientated to field geology, exploration techniques and data processing, and also includes elements of sustainability, transversal societal and regulatory aspects. The program also focuses on EIT Overarching Learning Outcomes (OLO-s), which are embedded as core elements of the curriculum (innovation, entrepreneurship, sustainability, creativity, leadership and intercultural competencies). Significant contributions to the OLOs also arise from cross-organizational program elements, including the Exploration Entrepreneurship course, summer field camp, the Internship and the Social and Civic internship.